2010
DOI: 10.1016/j.neulet.2010.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Lamotrigine blocks the initiation and expression of repeated high-dose methamphetamine-induced prepulse inhibition deficit in rats

Abstract: Our group developed a new psychostimulant animal model reflecting some clinical aspects of schizophrenia better than the conventional model does. In this model, long-lasting prepulse inhibition (PPI) deficit at the basement state is induced via repeated administration of methamphetamine (METH, 2.5 mg/kg) without challenge injection of this psychostimulant. This study elucidates the effects of lamotrigine (LTG, 30 mg/kg) on the initiation and expression of a steady-state PPI deficit induced by the repeated METH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…In addition, a clinical trial demonstrated that administration of LTG along with stable clozapine exhibited a beneficial effect on the psychopathological symptoms of clozapine-resistant schizophrenic patients [32]. Our recent report described that prepulse inhibition deficit induced by repeated METH is prevented by repeated LTG co-administration and that it is recovered by acute LTG administration [24]. However, the effects of LTG on METH-induced glutamate release and apoptosis remain unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a clinical trial demonstrated that administration of LTG along with stable clozapine exhibited a beneficial effect on the psychopathological symptoms of clozapine-resistant schizophrenic patients [32]. Our recent report described that prepulse inhibition deficit induced by repeated METH is prevented by repeated LTG co-administration and that it is recovered by acute LTG administration [24]. However, the effects of LTG on METH-induced glutamate release and apoptosis remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Vehicles for METH and LTG were saline (1 ml/kg) and approximately 0.002 N HCl in distilled water (4 ml/kg), respectively. This study used dosages of METH (2.5 mg/kg) and LTG (30 mg/kg) that were chosen after considering the results obtained in previous studies [2,24].…”
Section: Introductionmentioning
confidence: 99%
“…The respective vehicles for METH and LTG were saline (1 ml/kg) and approximately 0.002 N HCl in distilled water (4 ml/kg). This study used dosages of METH (2.5 mg/kg) and LTG (30 mg/kg) that were chosen after considering the results obtained from previous studies [15,16].…”
Section: Methodsmentioning
confidence: 99%
“…In an animal model, LTG plus clozapine decreased hyperlocomotion induced by the NMDA receptor antagonist phencyclidine in rats [25]. Our recent report described that prepulse inhibition deficit and the increase of TUNEL-positive cells in the mPFC induced by repeated administration of 2.5 mg/kg of METH are prevented by repeated co-administration of LTG [15,16]. Moreover, our group presented data showing that LTG inhibits increased extracellular glutamate levels in the mPFC induced by 2.5 mg/kg of METH [16].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation